Isolation and Characterization of Microorganisms Involved in Biogas Production from Agricultural Waste (International Journal of Scientific Research in Science and Technology, 2024)
The study aimed to investigate the microbial composition involved in the biogas production process using a diverse range of substrates, including Spinacia oleracea (vegetable), banana peel, plant extract, watermelon residue, wheat straw and paddy straw, sourced from multiple locations in Jaunpur. Over a period of five weeks (30 days), the research employed established microbiological methodologies and customized anaerobic bio-digesters for the comprehensive analysis of the isolates and substrates to assess biogas generation. The evaluation revealed dynamic fluctuations in the digester temperature within the range of 30°C to 36°C, accompanied by initial pH levels ranging from 4.2 to 8.3, which subsequently decreased to pH 5-6 during and after the anaerobic digestion process. The identified anaerobic bacterial species encompassed Staphylococcus sp., Micrococcus, Enterobacter, Escherichia, Citrobacter, Bacillus sp., and Pseudomonas aeruginosa. Furthermore, the findings demonstrated a hierarchy in the percentage of biogas yield from the substrates, with the following ranking: synergistic mixture > plant extract > banana > wheat straw > spinach > watermelon. Notable disparity in the volume of biogas produced was observed across different substrate treatments and digestion periods. The research underscored the pivotal role of methanogens and other auxiliary bacteria in the overall biogas production process. Additionally, the average pH levels were determined to range between 6.3 - 7.2 before and 5.0 - 6.2 during and after anaerobic digestion. The observed decline in pH during the anaerobic digestion process was associated with the production of metabolites such as acetate, hydrogen gas, carbon dioxide and other volatile fatty acids, exerting significant influence on the substrates within the digesters.
Keywords: Agricultural Wastes; Biogas Digester; Methanogenic bacteria; Biogas production; Anaerobic digestion; pH range; Isolation and characterization